Analisis Framing Pemberitaan Menteri Agama Di Detik.Com Dan Tribunnews Tentang Analogi Kebisingan Azan Dengan Suara Anjing - Wahyu Nurazwan Setiyadi; Asna Istya Istya Marwantika (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2022)
The statement of the Minister of Religious Affairs, Yaqut Cholil Qoumas in February 2022 about the analogy of the sound of azan with the sound of dogs also triggered polemics in Indonesian society. The minister's statement was also amplified by online media and became a topic of public conversation on social media in the range of February 22-26, 2022. This study aims to analyze the reporting of the Minister of Religious Affairs' statements in online media Detik.com and Tribunnews.com. The method used is a qualitative method with a news text analysis approach using the framing analysis of Zhondang Pan and Gerald M. Kosicki. The result of the study was that Detik.com and Republika Tribunnews used different aspects of framing the news. Detik.com frames the news by focusing on things that are considered more attractive to readers. Tribunnews framed the news by deepening the discussion of the case by presenting more diverse sources ranging from the pros to the cons with the Minister. The framing comparison between the two is Detik.com highlight the opinions of sources who have a better chance of attracting readers or in other words tend to focus more on what is viral. Meanwhile, Tribunnews prefers a coherent news construction and not only focuses on viral statements but discusses in more detail from various parties both pro and contra with the statement of Minister of Religious Affairs Yaqut Cholil Qoumas.